Hadronic Molecule Interpretation of Tcc+ and Its Beauty Partners - Huimin Ren; Fan Wu; Ruilin Zhu (Advances in High Energy Physics)
Motivated by the latest discovery of a new tetraquark Tcc+ with two charm quarks and two light antiquarks by LHCb Collaboration, we investigated the DD∗ hadronic molecule interpretation of Tcc+. By calculation, the mass and the decay width of this new structure Tcc+ can be understood in one-meson exchange potential model. The binding energies for these DD∗ hadronic molecules with JP=1+ are around 1 MeV. Besides, we also studied the possible beauty partners Tbb10598 of hadronic molecule Tcc+, which may be feasible in future LHCb experiments.